WATER QUALITY ASSESSMENT OF LAR STREAM, KASHMIR USING MACRO INVERTEBRATES AS VARIABLE TOLERANTS TO DIVERSE LEVELS OF POLLUTION - Gaine, Muzaffar A.; Pal, Amit Kumar; Pandit, Ashok Kumar (Ecoprint: An International Journal of Ecology, 2014)
The present study conducted on “Lar stream” which is one of the principal left bank tributaries of the river Jhelum in the Valley of Kashmir (northern India), was an attempt to assess the water quality of the canal by using macro invertebrates present in the ecosystem. During the present study, a total of 26 species of macro invertebrates were registered from Lar stream which belonged to the orders Diptera, Trichoptera, Hirudinae, Ephemeroptera, Plecoptera, Gastropoda, Coleoptera, Arachnida, Lepidoptera, Crustacea, and Oligochaeta. Among all the eleven orders, Dipterans registered a highest of 7 species (27%) and was the most dominant order. Then trend was followed by Trichoptera which registered a total of 5 species (19%) and was the second most dominating group. Similarly, Ephemeroptera, Oligochaeta, Hirudinae, Plecoptera and Gastropoda which registered 2 species (8%) each were the next dominating orders. The least representing taxa were Coleoptera, Arachnida, Lepidoptera and Crustacea which registered only one species (4%) each during the entire study period. The present study concludes that presence of some pollution indicator species such as Tubifex tubifex, Limnodrilus sp. (among Annelida), Chironomous sp., Tabanus sp. etc. (among Arhropoda), Lymnea sp. (among Mollusca) point the changing status of the stream from non-polluted to polluted. DOI: http://dx.doi.org/10.3126/eco.v20i0.11326 Ecoprint An International Journal of Ecology Vol. 20, 2013Page : 19-26